Satellite Cells CD44 Positive Drive Muscle Regeneration in Osteoarthritis Patients - Manuel Scimeca; Elena Bonanno; Eleonora Piccirilli; Jacopo Baldi; Alessandro Mauriello; Augusto Orlandi; Virginia Tancredi; Elena Gasbarra; Umberto Tarantino (Stem Cells International)
Age-related bone diseases, such as osteoarthritis and osteoporosis, are strongly associated with sarcopenia and muscle fiber atrophy. In this study, we analyzed muscle biopsies in order to demonstrate that, in osteoarthritis patients, both osteophytes formation and regenerative properties of muscle stem cells are related to the same factors. In particular, thanks to immunohistochemistry, transmission electron microscopy, and immunogold labeling we investigated the role of BMP-2 in muscle stem cells activity. In patients with osteoarthritis both immunohistochemistry and transmission electron microscopy allowed us to note a higher number of CD44 positive satellite muscle cells forming syncytium. Moreover, the perinuclear and cytoplasmic expression of BMP-2 assessed by in situ molecular characterization of satellite cells syncytia suggest a very strict correlation between BMP-2 expression and muscle regeneration capability. Summing up, the higher BMP-2 expression in osteoarthritic patients could explain the increased bone mineral density as well as decreased muscle atrophy in osteoarthrosic patients. In conclusion, our results suggest that the control of physiological BMP-2 balance between bone and muscle tissues may be considered as a potential pharmacological target in bone-muscle related pathology.